2021
DOI: 10.1111/een.13072
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐resource network between Xylocopa bees and plant resources: generalist species, specialist individuals?

Abstract: 1. The resource partitioning hypothesis states that sympatric, morphologically, and functionally similar species can coexist by temporal separation or low food overlap. Also, the interindividual variations about the use of resources, i.e. individual specialisation, can promote the resilience and stability of their populations when an environmental disturbance affects food availability.2. Two sympatric and polylectic species of carpenter bees to test both the hypotheses of food niche partitioning and the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
1
4
0
3
Order By: Relevance
“…However, each single female was highly specialised since only four bees out of 45 females were detected carrying pollen belonging to two different sources in similar percentages, indicating concomitant pollen collection in the same day of sampling. Similar results were documented for two sympatric Xylocopa species in Brazilian savannah areas, where both species presented generalist diets but females were highly specialised (Araújo et al 2021). Specialist individuals are able to select and canalise information more e ciently when seeking resources in comparison to generalists (Bernays 2001), what could represent a pertinent advantage to optimise foraging strategies.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, each single female was highly specialised since only four bees out of 45 females were detected carrying pollen belonging to two different sources in similar percentages, indicating concomitant pollen collection in the same day of sampling. Similar results were documented for two sympatric Xylocopa species in Brazilian savannah areas, where both species presented generalist diets but females were highly specialised (Araújo et al 2021). Specialist individuals are able to select and canalise information more e ciently when seeking resources in comparison to generalists (Bernays 2001), what could represent a pertinent advantage to optimise foraging strategies.…”
Section: Discussionsupporting
confidence: 79%
“…One important aspect to be discussed is that regardless of the P. graminea polylecty, females concentrated their pollen collection on few plant species such as P. granulosum, a common tree species used in Uberlândia afforestation. Likewise, other generalist bee species such as Tetrapedia diversipes Klug (Rocha-Filho and Garófalo 2016), Xylocopa frontalis (Olivier), and X. grisescens Lepeletier (Araújo et al 2021) also exhibited selective diets, which could be a re ection of the long blooming period of their preferred pollen sources, as observed for Pereskia grandifolia Haw. (Cactaceae), the main species visited by T. diversipes females (Rocha-Filho et al 2016), and also in the present study for P. granulosum, which was represented by few individuals at the campus, but had long lasting owerings.…”
Section: Discussionmentioning
confidence: 84%
“…One factor that may contribute to the reproductive success of A. mekongensis , in spite of its small population size, is low competition for pollinators, as there are few other plant species in bloom in our study area during the flowering period of A. mekongensis . Another important factor may be high pollinator fidelity, as A. mekongensis appears to be pollinated almost exclusively by carpenter bees, which have been shown to demonstrate high floral fidelity ( Araújo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that A. versicolor and A. mekongensis were both visited almost exclusively by Xylocopa bees over both study years indicates that these morning glory species are specialists in terms of their pollinators. On the other end of the interaction, Xylocopa have been shown to be generalist foragers at the species level, visiting a large number of plant species ( Stewart et al 2018 ; Araújo et al 2021 ). Memmott et al (2004) examined plant pollinator networks and found that specialist species tend to interact with generalist species, as observed in our study system, which helps buffer against species extinctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation